Anomaly technique for expression the Indian Ocean Dipole in South Java Sea - Sartimbul, Aida; Rohadi, Erfan; Firdaus Ali, Mochammad; Khaidar, Zulfan (International Journal of Engineering and Technology, 2018)
The longer period of time series of anomaly data was usually used to express the climatic phenomena. Even it is common, however, there were limited study discusses how powerful anomaly technique for understanding the climatic phenomena that occur in the period of time.  The objective of this study is to understand the nature of anomaly, to identify an unusual fluctuation of data, and to detect the climate change impact to the Sea Surface Temperature (SST). The eleven years satellite Aqua Modis data and Dipole Mode Index were applied to this study.  The raw data were averaged and removed seasonal trend using anomaly technique and then plotted to both MS Excel and Surfer ver. 6. The result shows that the monthly average of SST was indicated a seasonal/ sinusoidal pattern. Furthermore, anomaly analysis provides an unusual SST trend that has a direct impact on the climatic phenomenon as Indian Ocean Dipole. It is suggested that an anomaly technique may provide a good tool for expression unusual phenomena due to climate change.
Keywords: Anomaly; Average; Climate change; SST; Time series